Role of Partner and Health Workers on Modern Contraceptive Use Among Married/In-union Women in Uzbekistan - Supriatin, Supriatin; Rifky, Mohamed; Khan, Muhammad Uzair; Amaliah, Lili; Nurmalita Sari, Marlynda Happy; Santoso, Eko Budi; Ruswandi, Indra; Maretalinia, Maretalinia; Suwarni, Linda (UI Scholars Hub, 2023)
Many factors contribute to the declining total fertility rate, including family planning programs. The successful implementation of the family planning method might be influenced by how the decision to choose a contraceptive method was made. This study aimed to examine the correlation between family planning decision-makers and modern contraceptive use among married/in-union women of reproductive age in Uzbekistan. The 2021-2022 Multiple Indicator Cluster Survey was used by selecting only married/in-union women of reproductive age of 15 to 49 years, totaling 2,794 eligible samples. The modern family planning use variables were divided into not using, using Long-Acting Contraceptives (LAC), and Short-Acting Contraceptives (SAC). The univariate, bivariate (Chi-square and ANOVA), and multinomial logistic regression were performed. Family planning decision-makers from both women and husbands/partners, healthworkers, or others were significantly associated with modern contraceptive use for SAC and LAC, respectively. The type of family planning methods was significantly influenced by decision makers. Spouses, family members, and health workers need to implicate women to decide the most applicable contraceptive method.